Understanding the Research Data Management Practices of Researchers in the Department of Historical Studies at the University of Cape Town - Thomson, Ingrid (University of Cape Town, 2025)
The aim of the study was to investigate the current research data management practices in the Department of Historical Studies at the University of Cape Town. The purpose of the study was an exploration of the research data management practices in the Department particularly in light of the University of Cape Town's research data management policy. The objectives were to understand the research practices of the researchers and whether and how the act of research data management is incorporated into the current research practices and perspectives of historical scholarship within the Department and whatsupport they needed from the University of Cape Town Libraries. There is a dearth of literature covering research data management and historical studies and this study adds to the field of research data management in Humanities of which historical studies is a part. The research design employed was that of a case study. Data was collected through semi-structured interviews of individual history staff, while data collected from students was through focus groups. The data was analysed according to themes which were identified by the questions guiding the study, the literature review, the research data management lifecycle and the history research lifecycle theory that supported the study. The study findings showed that, while not calling the process data management, researchers were already managing their data as part of managing their research within the history research lifecycle. Findings also showed that there was limited awareness of the official research data management policy at the University of Cape Town, and where there was awareness, the policy was seen as a bureaucratic requirement. The researchers also had limited awareness of the support and services the University of Cape Town Libraries provided. The study recommends that there should be a domain-specific strategy towards research data management to take the disciplinary differences and culture of history into account, including the tailoring of a data management plan for history.